The Legal Nature of Model Laws of the Interparlamentary Assembly of States-Members of Commonwealth of Independent States - Antonova, Lyudmila (Research Papers, 2018)
The article shows based on the analysis of judicial practice that the model laws of the Interparliamentary Assembly of the Commonwealth of Independent States (CIS) are used not only in the lawmaking process, but in the law application of the courts. The article entitled the practice of application of the Model law on the treatment of animals. The absence of Federal law on this issue has led to the fact that not only the litigants but the courts of various subjects of the Russian Federation use the specified model law to justify their position.
Keywords: Model law; Court decision; National law; The legal force of federal law; The appeal determination